2015
DOI: 10.1121/1.4906250
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of the stimulus presentation rate on medial olivocochlear system assays

Abstract: Click evoked otoacoustic emissions (CEOAEs) are commonly used both in research and clinics to assay the medial olivocochlear system (MOC). Clicks presented at rates >50 Hz in the contralateral ear have previously been reported to evoke contralateral MOC activity. However, in typical MOC assays, clicks are presented in the ipsilateral ear in conjunction with MOC elicitor (noise) in the contralateral ear. The effect of click rates in such an arrangement is currently unknown. A forward masking paradigm was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Therefore, for OAE-based assays of the MOCR, it is critical that the presence of the MEMR is not based on MEMR thresholds obtained from clinical tympanometers. We emphasize that monitoring the OAE-evoking stimulus is currently the optimal solution to sensitive monitoring of MEMR activation, in keeping with previous recommendations (Guinan, 2010;Zhao and Dhar, 2012;Mertes and Goodman, 2015;Boothalingam and Purcell, 2015).…”
Section: Ivg Implications For Mocr Assayssupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, for OAE-based assays of the MOCR, it is critical that the presence of the MEMR is not based on MEMR thresholds obtained from clinical tympanometers. We emphasize that monitoring the OAE-evoking stimulus is currently the optimal solution to sensitive monitoring of MEMR activation, in keeping with previous recommendations (Guinan, 2010;Zhao and Dhar, 2012;Mertes and Goodman, 2015;Boothalingam and Purcell, 2015).…”
Section: Ivg Implications For Mocr Assayssupporting
confidence: 79%
“…As such, when frequency-specific changes are not considered (e.g., Boothalingam and Purcell, 2015;Mertes, 2020), MEMR detection may be less sensitive. This is because MEMR-induced stimulus changes at the lower and higher frequencies may partially cancel out and falsely reflect little or no change.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus presentation rate was Gaussian distributed from 9.1/s to 13.1/s with a mean rate of 11.1/s. This relatively slow range of presentation rates was selected to ensure that the stimuli did not temporally summate to activate the MOC reflex, which has been shown to affect OAE measurements at stimulus presentation rates as low as 30/s–50/s (Veuillet et al, 1991; Francis and Guinan, 2010; Boothalingam and Purcell, 2015). A Gaussian-distributed (i.e., “temporally jittered”) presentation rate was selected to facilitate subject alertness, as this may influence MOC reflex strength (Aedo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, Boothalingam et al (2014) found a trend of reduced contralateral inhibition of otoacoustic emissions (OAEs) elicited with single-tone stimuli (stimulus frequency OAEs) when the tones were AM versus unmodulated. No significant differences were seen in contralateral inhibition when elicited by a babble noise relative to white noise (Timpe-Syverson and Decker, 1999;Papsin et al, 2014), but these studies did not report sufficient controls for middle-ear muscle reflex activation which could interfere with the interpretation of results (Goodman et al, 2013) and the click stimulus rate of 50/s may have elicited the ipsilateral MOCR (Boothalingam and Purcell, 2015). A recent paper examined the effect of a variety of contralateral noises on contralateral inhibition (Kalaiah et al, 2017).…”
Section: Introductionmentioning
confidence: 98%